An exploratory study on the impact of ESG on business performance-Focusing on listed companies in Korea and Taiwan. - Shaojie Fan (PLoS ONE)
In the context of the ESG era, this study provides an in-depth analysis of the ESG practices of listed companies and their impact on business performance in Korea and Taiwan, two of the Four Little Dragons economies in Asia. Although these two regions are similar in terms of economic size, they show significant differences in their ESG implementation strategies and effects. Based on the Bloomberg database, this study empirically analyzes data from 113 Taiwanese and 113 Korean firms, using Tobin's q ratio as a measure of business performance. The findings show that there is complexity in the association between ESG scores and firms' business performance. In South Korea, government policies and large conglomerates contribute significantly to ESG practices, while in Taiwan, the economic structure dominated by SMEs has led to different characteristics of ESG practices. All of these differences reflect the influence of intra-firm factors on performance. The findings of this study not only enrich the theoretical foundation of the relationship between ESG and business performance, but the findings provide valuable regional insights and recommendations for international investors, corporate managers, and policymakers in the Asia-Pacific region to implement ESG strategies, especially when considering the specific market environment, economic structure, and internal factors of the firms they operate in order to achieve sustainable growth and competitive advantage.